Sosialisasi Pemahaman Doa Rosario Sebagai Kontemplasi Dan Dampaknya Bagi Perkembangan Iman Umat Di Uma-Mahon Ismaik Ba Ema Liquica – Timor Leste - Theodorus A. Silab (CV. Multi Kreasi Media, 2023)
One of the well-known Catholic devotions is praying the Rosary. Catholics are used to praying the rosary but do not understand the idea of ​​praying the rosary as contemplation. Pope Paul VI really hopes that the Rosary will be lived as a prayer of contemplation because it is related to reflection on the mystery of the life of Jesus Christ as written in the Holy Scriptures. Ideally, praying a good rosary is at the same time contemplating the mystery of Christ. This aspect is unknown to most Catholics, even though they are used to praying. One group of Catholics who are not aware of this idea is the ISMAIK group which manages a home for the sick in Liquica, Timor Leste. Activities to socialize the understanding of the rosary as contemplation are carried out in order to help people understand this idea and live it in praying the rosary. The results of the socialization show that these service partners now understand the rosary as a prayer of contemplation. This understanding helps people to appreciate the prayer of the Rosary by contemplating the mystery of Jesus when praying the Rosary together.